Projek Penguatan Profil Pelajar Pancasila Sebagai Program Kokurikuler Di Jenjang Sekolah Dasar - Indani Damayanti; Muhammad Iqbal Al Ghozali (Elementary Teacher Education Program, Majalengka University, 2023)
This study raises the teacher's perception of the Projek Penguatan Profil Pelajar Pancasila (P5) as a co-curricular program in the implementation of the merdeka curriculum on the indicators of its objectives, content, process and evaluation. This is based on the importance of understanding P5 as a co-curricular program that can strengthen character and competence. To gather data, this study used a quantitative descriptive research method, in which data collection was carried out by distributing questionnaires to 100 elementary school teachers in Cimahi city, then conducting limited interviews to 3 sample teachers to strengthen the questionnaire. Based on the findings, it shows that the teacher's perception of P5 in terms of indicators of co-curricular understanding, P5 objective indicators, P5 content indicators, P5 process indicators and P5 evaluation indicators are in the sufficient category. This was reinforced by the results of the interviews which showed that teachers did not understand the P5 plot, the P5 module components, and the P5 activity syntax. Thus the teacher's perception of P5 is still categorized as sufficient or not good. For this reason, efforts are needed to increase teachers' understanding of P5, one of which is through the use of the Platform Merdeka Mengajar as a medium for independent teacher training which can be done anywhere and anytime. The use of the Platform Merdeka Mengajar is expected to improve teachers' perceptions of P5 as a co-curricular program in the merdeka curriculum.